Daniel and the "schemes": Illegalisms and complementary transportation in the suburbs of Rio de Janeiro - Rodrigues , Eduardo de Oliveira (Seven Editora, 2024)
Cities around the world have different times that are articulated in the construction of their daily lives. This dialectic between speed and slowness can be perceived in several ways, including the careful observation of their modes of transport. They allow the operation of different regimes of movement of people and goods, and that, in the case of a city like Rio de Janeiro, cannot be understood without the contribution of vans and kombis to its transport system. These complementary modes reproduce even more clearly the dialectic between speed and slowness, especially due to an element that makes a difference: the combination of a series of illegalisms in their operationalization. In this sense, this paper aims to understand the tactics that enable the entanglement of a complementary transport "scheme" in the suburbs of Rio de Janeiro – a region of the capital of Rio de Janeiro that encompasses dozens of neighborhoods geographically and symbolically distant from the "center" of the metropolis and its wealthier tourist neighborhoods. I seek to describe the operation of this market embedded in the borders of the legal/extralegal as a way of thinking about the different times that shape the illegalisms that cross Daniel’s relationship (a van driver who aims to be a military policeman) with the city. This exercise allows us to shed light on some dimensions of the complementary transport market in Rio de Janeiro from the point of view of a possible future "policeman" who was already experiencing a daily work marked by precariousness and violence. This text presents part of the results of my doctoral thesis, built on ethnographic fieldwork carried out in the environment of a "preparatory course" for the next competition of the Military Police of the State of Rio de Janeiro (PMERJ). My interlocutors are not "recruits" already enrolled in police training schools, but simple young people between the ages of 18 and 32 who aim, for various reasons, to join the PMERJ. Over the course of fifteen uninterrupted months (nine face-to-face and six "remote"), I tried to understand the motivations that lead these young people to want to pursue this profession before any formal contact with the military corporation. Thus, the structure of the text seeks to outline a leaner analytical approach to this problem, bringing the interests in the police career from the perspective of a van driver. The narrative develops through the accompaniment of an afternoon in Daniel’s van, when I was designated his "ticket collector" within the route traveled by him daily within the scope of his work. DOI:https://doi.org/10.56238/sevened2024.007-014